Analisis Semiotika: Representasi Nilai-Nilai Harapan Terhadap Keyakinan Dalam Film Kamen Rider Gotchard - Muhammad Baby Febrio; Fitriyanto Fitriyanto; Yudha Febri Al Paksi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the representation of hope values in belief in the film Kamen Rider Gotchard using Charles Sanders Peirce's semiotic approach. The film was chosen because it contains many symbols, representations, and implicit messages related to hope and belief, particularly through character interactions and its plot. The research method used is descriptive qualitative, with data collection techniques through observation and documentation of film Scenes. This study adopts a constructivist approach in its implementation. The results show that hope in belief is represented in three main forms: (1) Hope to strive, which motivates the main character to keep trying despite obstacles; (2) Hope to rise, depicting how characters overcome failures and setbacks; and (3) Hope to sacrifice, reflected in characters' sacrifices for the safety of others or a greater purpose. This representation is analyzed through Peirce's triadic triangle: Sign, Object, and Interpretant. The conclusion of this study is that Kamen Rider Gotchard is not only entertaining but also conveys a profound message about the importance of hope in building self-belief and inspiring others. This research is expected to serve as a source of information for academics, communication professionals, and the general public in understanding the meaning of hope values through Sign analysis.